2015
DOI: 10.1177/0030222814568274
|View full text |Cite
|
Sign up to set email alerts
|

The “How” and “When” of Parental Loss in Adulthood

Abstract: In order to evaluate the role of cause of death on the grief responses of parentally bereaved young and middle-aged adults, 400 individuals completed measures assessing their experiences and feelings surrounding the loss of a parent. Respondents included 247 young adults and 155 middle-aged adults. Cause of death was categorized as acute or anticipated with 209 participants reporting the parent's death as acute, while anticipated death was reported by 191 individuals. Results suggested that gender of the adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
2
12
0
1
Order By: Relevance
“…Being in a stable, romantic relationship might have helped participants cope with the bereavement. Research has shown that individuals in romantic relationships had higher self-esteem and life satisfaction levels than singles (Dush & Amato, 2005; Harris & Orth, 2019) and that they were less negatively impacted after the loss of a parent (Hayslip et al, 2015). In addition, participants who were strongly impacted by a bereavement might have withdrawn or dropped out.…”
Section: Discussionmentioning
confidence: 99%
“…Being in a stable, romantic relationship might have helped participants cope with the bereavement. Research has shown that individuals in romantic relationships had higher self-esteem and life satisfaction levels than singles (Dush & Amato, 2005; Harris & Orth, 2019) and that they were less negatively impacted after the loss of a parent (Hayslip et al, 2015). In addition, participants who were strongly impacted by a bereavement might have withdrawn or dropped out.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that individuals in romantic relationships had higher self-esteem and life satisfaction levels than singles (Dush & Amato, 2005;Harris & Orth, 2019) and that they were less negatively impacted after the loss of a parent (Hayslip, Pruett, & Caballero, 2015).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…As parent–child relationships represent lifelong bonds, parental death is often considered a major stressor—a distressing event that can challenge people's adaptive capacities (Pearlin, ; Umberson, ). Following the death of a parent, individuals report thoughts and emotions associated with grief (e.g., existential loss; guilt, blame, and anger; preoccupation with thoughts of the deceased; Carver, Hayslip, Gilley, & Watts, ), symptoms of anxiety and depression (Hayslip, Pruett, & Caballero, ), a decrease in life satisfaction (Leopold & Lechner, ), and a decline in self‐esteem (Marks et al, ).…”
Section: Bereavement Responses To Death Of An Older Parentmentioning
confidence: 99%
“…Individuals who have a more neurotic personality tend to report more negative and ambivalent relationship qualities with their grown children (Birditt, Hartnett, Fingerman, Zarit, & Antonucci, ; Fingerman, Pitzer, Lefkowitz, Birditt, & Mroczek, ). The impact of the loss tends to be greater if the relationships to the deceased were emotionally significant (Bowen, ; Hayslip et al, ; Stokes, ). Furthermore, the negative effects of parental death on individuals' subjective well‐being tend to mitigate over time (Leopold & Lechner, ).…”
Section: Other Factors Associated With Intergenerational Relationshipmentioning
confidence: 99%